A Postcolonial Archive? On the Paradox of Practice in a Northwest Alaska Project - Kurtz, Matthew (Archivaria, 2006)
In this paper, I explore contradictions between postcolonialism and the institutional practices in the creation of an oral history archive in northwest Alaska. As a project, postcolonialism often harnesses an interpretive de-centring of the resources that power has colonized. The materiality of a local institutional archive, on the other hand, is created through the geographical centring of historical material. The production of such an archive thereby renders one effect most visibly: the constitution of his- torical subjects. To what extent do these two projects – postcolonialism and the making of an archive – then work toward different purposes? The paper examines the ambiguities of postcolonialism first as an index of historical-geographical space, then as a collective intellectual project. To illustrate contradictions between postcolonialism and the making of an archive, the paper substantiates these considerations through an example: the contemporary production of an oral history archive in northwest Alaska. The example serves on both registers: as a project sited in what may be said to be a “postcolonial” geography, and as a potentially postcolonial endeavour. I argue that the first description is off the mark, and that institutional endeavours to build an oral history archive in northwest Alaska, while ostensibly working against a history of colonialism,nonetheless re-inscribe various powers of colonialism. RÉSUMÉ Dans ce texte, l’auteur aborde les contradictions entre le post-colonialisme et les pratiques institutionnelles dans la création d’une institution d’archives d’histoire orale dans le nord-ouest de l’Alaska. Comme projet, le post-colonialisme se sert souvent d’un décentrage interprétatif des ressources que le pouvoir a colonisées. La matérialité d’une institution archivistique locale, par contre, est créée par un centrage géographique du matériel historique. La production de ce genre d’archives rend évidente un effet particulier : la constitution de sujets historiques. Jusqu’à quel point ces deux projets – le post-colonialisme et la création d’un centre d’archives – travaillent-ils vers des buts différents? Ce texte examine les ambiguïtés du post-colonialisme d’abord comme un index de l’espace historico-géographique, et ensuite comme un projet intellectuel collectif. Afin d’illustrer les contradictions entre le post-colonialisme et la création des institutions d’archives, ce texte établit le bien-fondé de ces considérations par un exemple : la fondation contemporaine d’un centre d’archives d’histoire orale dans le nord-ouest de l’Alaska. Cet exemple s’inscrit également dans deux registres : comme un projet sis dans ce que l’on peut appeler une géographie « post-coloniale » et comme une entreprise potentiellement post-coloniale. L’auteur démontre que la première description est loin de la vérité, et que les entreprises institutionnelles pour créer des archives d’histoire orale dans le nord-ouest de l’Alaska – quoiqu’elles travaillent ostensiblement contre une histoire de colonialisme – réinscrivent toutefois divers pouvoirs de colonisation.